Pengkondisian Udara Rumah Tinggal di Semarang - Suyanto Suyanto; Sri Pramono (Universitas Ivet, 2020)
The air condition in residential or office buildings needs to be sought so that the conditions are fresh and comfortable for the residents. Indonesia with a tropical climate has hot temperatures and high humidity levels. For this reason, the application of air conditioning systems is needed. The study was conducted by survey to record the size of the house, the area of ventilation, the number and size of air conditioners used, the temperature of the use of air conditioners, and the monthly electricity bill. Data is processed to obtain specific data on the adequacy of ventilation, the level of ACusage, the temperature of AC usage, and the level of AC electricity usage. The results of this study are that 77% of residential houses have ventilation areas that meet minimum requirements. Houses that use AC as much as 60%. Almost all air conditioners are used in sleeping rooms. AC users mostly choose cool comfortable temperatures, which is 55%. As for whochose the temperature of the use of air conditioners in optimal comfortable conditions by 35%. While those who choose warm temperatures to comfort in the use of AC as much as 10%. The average electricity bill due to the use of AC is 34% of the total residential electricity bill.